A network model of financial system resilience - Kartik Anand; Prasanna Gai; Sujit Kapadia; Simon Brennan; Matthew Willison (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We examine the role of macroeconomic fluctuations, asset market liquidity, and network structure in determining contagion and aggregate losses in a financial system. Systemic instability is explored in a financial network comprising three distinct, but interconnected, sets of agents - domestic banks, international financial institutions, and firms. Calibrating the model to advanced country banking sector data, we obtain sensible aggregate loss distributions which are bimodal in nature. We demonstrate how systemic crises may occur and analyze how our results are influenced by firesale externalities and the feedback effects from curtailed lending in the macroeconomy. We also illustrate the resilience of our model financial system to stress scenarios with sharply rising corporate default rates and falling asset prices.
Keywords: C63; G01; G17; G21; 330; contagion; financial crises; network models; systemic risk; Finanzmarktkrise; Ansteckungseffekt; Bankensystem; Unternehmensnetzwerk; Konjunktur; Systemrisiko; Theorie